Role of the Cerebellum in Cognitive Function - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers in the Department of Psychology, University of Rome, Italy, retrospectively analyzed charts from patients in the Ataxia Lab of Santa Lucia Foundation between 1997 and 2007, focusing on the role of the cerebellum in cognition.